Development of a Non-invasive Methodology for the Assessment of Muscle Fibre Composition - Winkler, Tobias; Mersmann, Falk; von Roth, Philipp; Dietrich, Ralf; Bierbaum, Stefanie; Arampatzis, Adamantios (Frontiers in Physiology, 2019)
The percentage area of fast twitch fibres of a muscle is a major determinant of muscle mechanical power and, thus, an important biomarker for the evaluation of training processes. However, the invasive character of the assessment (muscle biopsy) limits the wide application of the biomarker in the training praxis. Our purpose was to develop a non-invasive method for the assessment of fast twitch fibre content in human soleus muscle. Maximum muscle mechanical power depends on the fibre composition, the muscle volume and muscle specific tension. Therefore, we hypothesised that the percentage area of type II fibres would show a high relationship with the maximum muscle mechanical power normalised to muscle volume and specific muscle contractile strength (i.e. plantar flexion moment divided by muscle cross-sectional area). In twenty male adults the percentage area of type II fibres, volume and maximum cross-sectional area of the soleus muscle as well as the maximum plantar flexion moment and the maximum mechanical power were measured using muscle biopsies, magnet resonance tomography, and dynamometry. The maximum mechanical power normalised to muscle volume and specific muscle contractile strength provided a significant relationship (r=0.654, p=0.002) with the percentage area of type II fibres. Although the proposed assessment-parameter cannot fully replace histological measurements, the predictive power of 43% can provide a relevant contribution to performance diagnostics in the training praxis.